Differential effects of TAK-442, a novel orally active direct factor Xa inhibitor, and ximelagatran, a thrombin inhibitor, on factor V-mediated feedback on coagulation cascade and bleeding - Konishi, Noriko; Hiroe, Katsuhiko; Kawamura, Masaki (Thrombosis and Haemostasis, 2010)
Thrombin amplifies the blood coagulation via factor V (FV)-mediated positive feedback loop. We hypothesised that factor Xa (FXa) inhibitors would interfere more gradually with this feedback activation loop than thrombin inhibitors, thereby achieving a better balance between haemostasis and prevention of thrombosis. In this study, we compared the effects of TAK-442, a novel FXa inhibitor, versus ximelagatran, a thrombin inhibitor, on FV-mediated positive feedback, venous thrombosis and bleeding. In normal plasma, TAK-442 delayed the onset of tissue factor-induced thrombin generation and prolonged prothrombin time (PT) with more gradual concentration-response curve than melagatran, the active form of ximelagatran. The effect of melagatran on the onset of thrombin generation decreased in an FVa-concentration-dependent manner in FV-deficient plasma supplemented with FVa. Furthermore, in FV-deficient plasma, the PT-prolonging potency of melagatran was markedly increased with a change in its concentration-response curve from steep to gradual. In the rat venous thrombosis model, TAK-442 (10 mg/kg, p.o.) prevented thrombus formation by 55% with 1.2 times prolongation of PT; a similar effect was observed in ximelagatran-treated (3 mg/kg, p.o.) rats. TAK-442 at 100 mg/kg prolonged PT by only 2.1 times with no change in bleeding time (BT), whereas ximelagatran at 10 mg/kg prolonged PT by 3.9 times and significantly increased BT. These results suggest that the differential effects of the two agents on FV-mediated amplification of thrombin generation may underlie the observation of a wider therapeutic window for TAK-442 than for ximelagatran.
Keywords: Anticoagulants; thrombosis; haemostasis; blood coagulation